Theoretical reflections on State and the territorial dimension of politics (Research, Society and Development, 2019)
This article aims to contribute to the theoretical reflections on the State and the dimensions of politics, highlighting its territorial dimension. This is a bibliographic research that sought to synthetically expose the different theoretical currents about State, from Political Geography to Political Science.